Digital Gold Investment and Islamic Ethics: A Behavioral Finance Perspective on Muslim Investor Decisions in Indonesia - Awis Hardjito; Zirlia Anggraini; Syamsul Arifin; Abdullah Yaqin (STAI Serdang Lubuk Pakam, 2026)
The growth of the digital gold market in Indonesia has attracted the interest of Muslim investors who are focused not only on financial gains but also on adherence to Islamic principles. However, research on the interaction between psychological factors and religious values in investment decision-making remains limited. This study aims to develop a conceptual framework that integrates the Theory of Planned Behavior (TPB), Islamic finance principles, and behavioral finance perspectives to explain digital gold investment behavior. This framework views religious values and cognitive biases as interacting factors in shaping perceptions, evaluations, and investment decisions. Based on Islamic teachings regarding justice, honesty, and the avoidance of speculative practices, this study argues that religious commitment can mitigate the influence of biases such as overconfidence, herding, and loss aversion. Furthermore, the implementation of Sharia compliance through transparency, clear asset ownership, and ethical accountability has the potential to encourage more rational and long-term-oriented investment behavior. This framework offers both theoretical contributions and practical implications for the development of a trustworthy, inclusive digital gold ecosystem that aligns with Islamic values.